Dual function of ammonium acetate in acetone-butanol-ethanol fermentation by Clostridium acetobutylicum. (November 2018) - Li, Shubo; Zhou, Yuan; Luo, Zhiting; Cui, Yanyan; Xu, Yu; Lin, Lihua; Zhao, Mouming; Guo, Yuan; Pang, Zongwen
Graphical abstract: Compared to the control, the introduction of ammonium ions could effectively down-regulate the relative expressions of six genes involved in butanol synthesis in the acidogenesis phase. Highlights: Ammonium acetate improves ABE fermentation as the sole nitrogen source. Ammonium acetate significantly inhibits ABE fermentation as the compound nitrogen source. NH4 + down-regulates the transcriptional levels of genes involved in butanol synthesis. Abstract: In this study, a compound nitrogen source, integrating the advantages of ammonium acetate and soybean meal, was proposed to further improve acetone-butanol-ethanol fermentation. Unfortunately, this compound nitrogen source was found to effectively inhibit cellular performance, as the introduction of NH4 + significantly decreased the yield of butanol and total solvents by 34.78% and 35.14%, to only 6.62 g/L and 10.76 g/L, respectively. Meanwhile, the regulatory mechanism was further elucidated at different levels. As a result, the NH4 + could down-regulate the transcriptional levels of key genes involved in butanol synthesis, and the activity of acetoacetyl-CoA/acyl-CoA transferase, and then decrease the accumulation of key intermediates. Therefore, ammonium acetate has a dual function in ABE fermentation, as it effectively improves ABE fermentation when it is the sole nitrogen source but significantly decreases fermentation performance in the presence of soybean meal, broadening the understanding of nitrogen regulation mechanism of C. acetobutylicum .